Recent advances in information systems and technologies. Volume 1 - Rocha, Álvaro; Correia, Ana Maria; Adeli, Hojjat, 1950-; Reis, Luís Paulo, 1970-; Costanzo, Sandra (Advances in intelligent systems and computing ;, 2017)
This book contains a selection of papers accepted for presentation and discussion at The 2017 World Conference on Information Systems and Technologies (WorldCIST'17). This conference had the support of the IEEE Systems, Man, and Cybernetics Society, AISTI (Iberian Association for Information Systems and Technologies/Associação Ibérica de Sistemas e Tecnologias de Informação), ISCAP (School of Accounting and Administration of Porto/Instituto Superior de Contabilidade e Administração do Porto), and GIIM (Global Institute for IT Management). It took place at Porto Santo Island, Madeira, Portugal, during April 11--13, 2017.